Potensi Pasraman Hindu sebagai Tujuan Pariwisata Spiritual - I Gede Sutarya (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2017)
Spiritual tourism is a phenomenon in a tourism by religious and spiritual purposes. Spiritual journey has become an ancient form of travelling, but new developments develop by wide segmentation. Hindu Pasraman such as Munivara and Ratu Bagus ashram have become a spiritual tourism destination. Therefore, its potentials need to be explored for the development of a larger Hindu pasraman. This study explores the potential of Hindu pasraman by comparing it with the motivation of foreign tourists. The potential that its developing seemly with the motivation of foreign tourists to be a potential that can be developed. This research uses datacollection by used literature studies, observations and interviews. The data analysis uses qualitative data analysis. The result of this research is the potential of pasraman Hindu as a place of learning, relaxation, and health is potential that can be developed to become a spiritual tourism destination. Continued research is expected to measure the most dominant potential. Through this research can be suggested to improve facilities, access, and cooperation of Hindu pasraman organization.